Variasi Dialek Bahasa Sasak di Beberapa Wilayah Pulau Lombok, Nusa Tenggara Barat: A Systematic Literature Review - Lalu Ahmad Zaini; Zulfikar Andi; Sri Wulandari (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
The Sasak language, spoken predominantly on Lombok Island, West Nusa Tenggara, represents one of Indonesia's linguistically rich regional languages characterized by extensive dialectal diversity. Numerous studies have identified lexical, phonological, morphological, syntactic, semantic, and pragmatic variations across different Sasak-speaking communities. However, previous investigations have generally focused on individual dialects or specific linguistic aspects, leaving limited comprehensive synthesis regarding dialectal variation throughout Lombok. Therefore, this study aims to systematically review scholarly publications discussing Sasak dialect variation across multiple regions of Lombok Island. This research employed a Systematic Literature Review (SLR) approach following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework. Twenty-nine peer-reviewed journal articles published between 2011 and 2025 were selected using predefined inclusion and exclusion criteria. Data were analyzed through qualitative thematic synthesis, emphasizing dialect classification, linguistic characteristics, geographical distribution, and sociolinguistic implications. The review demonstrates that Sasak consists of several major dialects, including Ngeno-Ngene, Meno-Mene, Nggeto-Nggete, Meriaq-Meriku, and Kuto-Kute, each exhibiting distinctive phonological, lexical, semantic, morphological, and syntactic characteristics influenced by geographical, historical, and sociocultural factors. Furthermore, recent studies indicate that dialect diversity presents both challenges and opportunities for language preservation, educational policy, digital language technology, and regional cultural identity. This review contributes an integrated framework for understanding Sasak dialect diversity while identifying future research directions concerning language documentation, standardization, computational linguistics, and sustainable preservation of regional languages.